Characterization of a wave soldering process using Taguchi method - Mohd. Rohani, Jafri; Syed Hassan, Syed Ahmad Helmi; Chan, Eu Lene (Faculty of Mechanical Engineering, 1999)
This paper outlines the Taguchi methodology as an approach to identify the "optimal" wave soldering machine parameter setting that has significant effect on a key quality characteristic of interest, namely, soldering defects per units (SDPU). The method is briefly discussed and its application is illustrated by an industrial case study as an example. Several machine controllable factors were investigated as to their effect on the SDPU. The result of the study shows an improvement of up to 70 percent of SDPU. Its potential in cost savings is the apparent.